Digital Marketplace Marketing Strategy for Underperforming Herbal Tea Products - Mahendrajit Yudhantoko; Atik Aprianingsing (Publikasi Indonesia, 2026)
This research examines marketplace visibility optimization strategies for JSR Rimpang Tea, an underperforming herbal wellness beverage sold on the Shopee platform in Indonesia. Despite strong perceived product quality, JSR Rimpang Tea experienced weak sales performance due primarily to limited algorithmic visibility, low organic discoverability, and insufficient social proof rather than product inadequacy. Using a mixed-methods case study approach, the research integrates quantitative marketplace performance data from Shopee Analytics, a consumer survey of 200 respondents, competitive benchmarking using the 4P marketing mix framework, and qualitative insights from structured interviews with the business owner. The findings reveal that Shopee's algorithmic mechanisms—particularly search ranking, engagement signals, and recommendation systems—play a decisive role in driving semi-impulsive purchase behavior in resource-constrained SME contexts. The study develops a prioritized, SME-oriented marketplace visibility optimization framework emphasizing high-impact, low-cost strategies such as keyword optimization, systematic review accumulation, value-tier pricing alignment, flash sale participation, and selective influencer collaborations. This framework provides practical guidance for SMEs with limited budgets and organizational capacity to improve visibility and sales performance. The study contributes context-specific insights into Indonesian e-commerce dynamics and offers actionable recommendations for enhancing digital marketplace performance in the functional herbal beverage category.